Narrativas urbanas: cidade, fotografia e memória, Toledo- PR (1950-1980) - Santos, Reginaldo Aparecido dos (2010)
This paper aims to discuss and analyze some main photographs that were selected and arranged by articulating the history museum city of Toledo, images given as "official" or an "official memory" in order to realize their strengths in the formation of a social imagery and the city. Highlights a set of photographs (photographs expressed in albums, banners and specific projects of the Museum Historical Willy Barth) circulating in the city through various forms and strategies, and you end up impregnating this social imaginary of the "early days", to constitute a "culture of memory". Thus, we reflect on the history of the city of Toledo, disregarding the imagined, the visible, not visible, present in narratives about urban expressed in photographs from the 1950s, and are disseminated mainly from the 1980s, with the creation of the museum and the investment of this "culture of memory" in the city. These photographs, many of them insistently repeated, demonstrate the strength and role of this institution in the reproduction of social imaginary of the city, establishing strategies that target the residents look for a particular month. This results in social representations of the city, established primarily for the use and propagation of selected photos arranged and this time, trying to legitimize a specific reality of that period, highlighting some elements of excellence, where the reference and urban transformation, emphasizing the modernization in which would be passing the municipality. The selected photographs, specifically in its arrangement, establish a sense of past that is desired and that tries to be remembered, in the establishment of an urban imagination. If before it was aimed a look to the future in the 1950s, the 1980s, there is a systematic return to a past that sought to be recovered